The influence of riparian evapotranspiration on stream hydrology and nitrogen retention in a subhumid Mediterranean catchment - A. Lupon; S. Bernal; S. Poblador; E. Martí; F. Sabater (Hydrology and Earth System Sciences, 2016)
Riparian evapotranspiration (ET) can influence stream hydrology at catchment scale by promoting the net loss of water from the stream towards the riparian zone (i.e., stream hydrological retention). However, the consequences of stream hydrological retention on nitrogen dynamics are not well understood. To fill this gap of knowledge, we investigated changes in riparian ET, stream discharge, and nutrient chemistry in two contiguous reaches (headwater and valley) with contrasted riparian forest size in a small forested Mediterranean catchment. Additionally, riparian groundwater level (hgw) was measured at the valley reach. The temporal pattern of riparian ET was similar between reaches, and was positively correlated with hgw (ρ  =  0.60) and negatively correlated with net riparian groundwater inputs (ρ  <  −0.55). During the vegetative period, stream hydrological retention occurred mostly at the valley reach (59 % of the time), and was accompanied by in-stream nitrate release and ammonium uptake. During the dormant period, when the stream gained water from riparian groundwater, results showed small influences of riparian ET on stream hydrology and nitrogen concentrations. Despite being a small component of annual water budgets (4.5 %), our results highlight that riparian ET drives stream and groundwater hydrology in this Mediterranean catchment and, furthermore, question the potential of the riparian zone as a natural filter of nitrogen loads.